Effects of adrenolytic mitotane on drug elimination pathways assessed in vitro - Theile, Dirk; Haefeli, Walter E.; Weiß, Johanna (Endocrine, 2015)
Mitotane (1,1-dichloro-2-(o-chlorophenyl)-2-(p-chlorophenyl)ethane, o,p′-DDD) represents one of the most active drugs for the treatment of adrenocortical carcinoma. Its metabolites 1,1-(o,p′-dichlorodiphenyl) acetic acid (=o,p′-DDA) and 1,1-(o,p′-dichlorodiphenyl)-2,2 dichloroethene (=o,p′-DDE) partly contribute to its pharmacological effects. Because mitotane has a narrow therapeutic index and causes pharmacokinetic drug-drug interactions, knowledge about these compounds’ effects on drug metabolizing and transporting proteins is crucial. Using quantitative real-time polymerase chain reaction, our study confirmed the strong inducing effects of o,p′-DDD on mRNA expression of cytochrome P450 3A4 (CYP3A4, 30-fold) and demonstrated that other enzymes and transporters are also induced (e.g., CYP1A2, 8.4-fold; ABCG2 (encoding breast resistance cancer protein, BCRP), 4.2-fold; ABCB1 (encoding P-glycoprotein, P-gp) 3.4-fold). P-gp induction was confirmed at the protein level. o,p′-DDE revealed a similar induction profile, however, with less potency and o,p′-DDA had only minor effects. Reporter gene assays clearly confirmed o,p′-DDD to be a PXR activator and for the first time demonstrated that o,p′-DDE and o,p′-DDA also activate PXR albeit with lower potency. Using isolated, recombinant CYP enzymes, o,p′-DDD and o,p′-DDE were shown to strongly inhibit CYP2C19 (IC50 = 0.05 and 0.09 µM). o,p′-DDA exhibited only minor inhibitory effects. In addition, o,p′-DDD, o,p′-DDE, and o,p′-DDA are demonstrated to be neither substrates nor inhibitors of BCRP or P-gp function. In summary, o,p′-DDD and o,p′-DDE might be potential perpetrators in pharmacokinetic drug-drug interactions through induction of drug-metabolizing enzymes or drug transporters and by potent inhibition of CYP2C19. In tumors over-expressing BCRP or P-gp, o,p′-DDD and its metabolites should retain their efficacy due to a lack of substrate characteristics.
Published online: 27 December 2014
Gesehen am 30.06.2020